2015
DOI: 10.3906/zoo-1412-15
|View full text |Cite
|
Sign up to set email alerts
|

Length–weight relationships of forty-nine fish species from shallow waters ofGökçeada Island, northern Aegean Sea

Abstract: Length-weight relationships (LWRs) of fishes provide important information for many studies in a given geographic region, such as comparing the condition, fatness, estimation of weight-at-age from total reported catch weight, and length-frequency distributions (Tesch, 1968), as well as for interregional life-history comparisons (Petrakis and Stergiou, 1995). The relationships may change temporarily and/or spatially, and for this reason should be regularly updated (Ismen et al., 2007). The northern Aegean Sea i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
2
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 7 publications
1
17
2
3
Order By: Relevance
“…Bauchot [21] reported that maximum total length of A. kessleri for males/unsexed as 10.0 cm in Mediterranean. However, Altın et al [17] found that maximum total length of A. kessleri from Gökçeada Island (northern Aegean Sea, Turkey) was 11.2 cm. The present study showed that the maximum total length of the species can extend to 11.9 cm for males and 11.8 for females.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bauchot [21] reported that maximum total length of A. kessleri for males/unsexed as 10.0 cm in Mediterranean. However, Altın et al [17] found that maximum total length of A. kessleri from Gökçeada Island (northern Aegean Sea, Turkey) was 11.2 cm. The present study showed that the maximum total length of the species can extend to 11.9 cm for males and 11.8 for females.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies on the length weight relationships of various populations of A. kessleri in Turkish Seas were reported previously [12][13][14][15][16][17]. Nevertheless, the sex ratio and the condition of the fish have not been included in previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…Countries Length-weight relationship Isometric growth Current study Gulf of Annaba (Algeria) TW = 0.008 TL 3.066 Gordo et al, 2016 Atlantic (Portuguese coast) TW = 0.0097 TL 3.05 Oztekin et al, 2016 Aegean sea, Turkey TW = 0.0164 TL 2.90 Akalin et al, 2015 Candarli Bay, Turkey TW = 0.0091 TL 3.09 Cengiz, 2013 Gallipoli, Turkey TW = 0.0116 TL 3.03 Bök et al, 2011 Marmara Sea, Turkey TW = 0.0091 TL 3.18 Çakir et al, 2008 Edremit bay, Turkey TW = 7. 10 -5 TL 2.62 Ismen et al, 2007 Saros bay, Turkey TW = 0.0086 TL 3.06 Cicek et al, 2006 North East Mediterranean TW = 0.0131 TL 2.89 Karakulak et al, 2006 Aegean sea, Turkey TW = 0.0112 TL 2.99 Moutopoulos and Stergiou, 1998 Aegean sea, Turkey TW = 0.0107 TL 3.001 Negative allometry Altin et et al, 2015 Golfe d'Antalya, Turquie TW = 0.012 TL 2.90 Kapiris and Klaoudatos, 2011 Aegean sea, Turkey TW = 0.5. 10 -4 TL 2.71 Torcu-Koc et al, 2004 Edremit bay, Turkey TW = 0.0311 TL 2.67 Abdallah, 2002 Alexandria, Egypt TW = 0.039 TL 2.55 Moutopoulos and Stergiou, 2002 Aegean sea, Turkey TW = 0.0186 TL 2.805 Torcu et al, 1998 Edremit bay, Turkey TW = 0.0353 TL 2.61 Goncalves et al, 1997 Atlantic (Portuguese coast) TW = 0.7.…”
Section: Authorsmentioning
confidence: 99%
“…10 -4 TL 2.71 Torcu-Koc et al, 2004 Edremit bay, Turkey TW = 0.0311 TL 2.67 Abdallah, 2002 Alexandria, Egypt TW = 0.039 TL 2.55 Moutopoulos and Stergiou, 2002 Aegean sea, Turkey TW = 0.0186 TL 2.805 Torcu et al, 1998 Edremit bay, Turkey TW = 0.0353 TL 2.61 Goncalves et al, 1997 Atlantic (Portuguese coast) TW = 0.7. 10 -4 TL 2.66 Merella et al, 1997 Balearic Islands (Mediterranean) TW = 0.016 TL 2.82 Petrakis and Stergiou, 1995 Greece TW = 0.022 TL 2.92 Papaconstantinou et al, 1994 Aegean sea, Turkey TW = 0.0276 TL 2.725 Positive allometry Ozvarol, 2014 Antalya gulf, Turkey TW = 0.0091 TL 3.04 Sangan et al, 2007 North East Mediterranean TW = 0.0662 TL 3.22 However many studies recorded negative allometry in Mediterranean (Papaconstantinou et al, 1994;Petrakis, and Stergiou 1995;Merella et al, 1997;Torcu et al, 1998;Abdallah, 2002;Moutopoulos and Stergiou 2002;Torcu-Koc et al, 2004;Kapiris and Klaoudatos 2011;Altin et al, 2015), and in Atlantic (Goncalves et al, 1997) (Table 1). Only Sangan et al (2007) and Ozvarol (2014) showed that the weight of the individual fish grows faster than its lengths (majored allometric) (Table 1).…”
Section: Authorsmentioning
confidence: 99%
“…Understanding of the length-weight relationships (LWRs) and lengthlength relationships (LLRs) in fisheries science is necessary to estimate the biomass (Altin, Ayyildiz, Kale, & Alver, 2015;Froese, 2006;Froese, Tsikliras, & Stergiou, 2011;Hasankhani, Keivany, Daliri, Pouladi, & Soofiani, 2014;Sharma, Mir, Singh, Akhtar, & Pandey, 2015), and management and assessment of stocks that are important tools in fishery research (Ak, Kutlu, & Aydın, 2009). This relationship is generally presented by the equation W = aL b .…”
Section: Introductionmentioning
confidence: 99%